Experimental Observation and Simulation Model for Transient Characteristics of Negative-Capacitance in Ferroelectric HfZrO2 Capacitor - Kyungmin Jang; Nozomu Ueyama; Masaharu Kobayashi; Toshiro Hiramoto (IEEE Journal of the Electron Devices Society, 2018)
We have experimentally observed the negative-capacitance transient effect in a ferroelectric HfZrO2 (FE-HZO) capacitor and developed an equivalent circuit model based on the Landau- Khalatnikov (LK) theory. By considering multiple domains (MD) and domain interaction, an MD-LK model precisely reproduced the experimental dynamic characteristics in an FE-HZO capacitor with the various input voltage amplitude and external resistance. The MD-LK model was successfully validated as a dynamic model for FE-HZO capacitor. The MD-LK model is highly expected as a useful simulation model for the dynamic NCFET with a multi-domain FE-HZO gate insulator.